2005
DOI: 10.1097/00005082-200509000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guideline Adherence Before and After Implementation of the HEARTFELT (HEART Failure Effectiveness & Leadership Team) Intervention

Abstract: HEART Failure Effectiveness & Leadership Team (HEARTFELT) is a multifaceted intervention designed to improve adherence with the American College of Cardiology/American Heart Association practice guidelines for heart failure (HF). The purpose of this study was to assess differences in clinician adherence with clinical practice guidelines before and after implementation of HEARTFELT. A quasi-experimental, untreated control group design with separate pretest/posttest samples was employed at a community hospital i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The remaining 18 articles do not offer a framework or provide a reference for the use of the term 'unwarranted variation'. Only six of these articles [59][60][61][62][63][64] report on studies to identify medical practice variations, whereas the other 12 were editorials, commentaries, review papers, or research studies examining health care without specific attention to identifying practice variations [44,[65][66][67][68][69][70][71][72][73][74][75]. As these 32 articles do not offer criteria on what is or is not unwarranted variation, they will not be discussed further in this review.…”
Section: Are All Variations Bad?mentioning
confidence: 99%
“…The remaining 18 articles do not offer a framework or provide a reference for the use of the term 'unwarranted variation'. Only six of these articles [59][60][61][62][63][64] report on studies to identify medical practice variations, whereas the other 12 were editorials, commentaries, review papers, or research studies examining health care without specific attention to identifying practice variations [44,[65][66][67][68][69][70][71][72][73][74][75]. As these 32 articles do not offer criteria on what is or is not unwarranted variation, they will not be discussed further in this review.…”
Section: Are All Variations Bad?mentioning
confidence: 99%
“…In a recent report by the Institute of Medicine, recommendations include the need for evidence‐based practice to enable safe care (Committee on the Work Environment of Nurses and Patient Safety, Institute of Medicine of The National Academies 2004). Research continues to emerge that supports that the processes and outcomes of nursing care are better when informed by strong evidence (Berenholtz et al 2004; Dykes et al 2005; Herr et al 2004; Mehta et al 2002; Ribby 2006). Third, there is a hierarchy of evidence.…”
Section: What Is Ebp? Why Is It So Important?mentioning
confidence: 99%
“…Asch et al however using this design was able to demonstrate the benefits of a collaborative organizational care intervention in CHF [12]. Other small but limited examples for CHF have also been published [12][13][14][15].…”
Section: Monitoring Patients Status and Response To Treatmentmentioning
confidence: 98%
“…For cardiovascular disease as a whole, some large studies have been reported, mostly positive [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], although longer term translation of findings into actual clinical care within those systems is unknown.…”
Section: Monitoring Patients Status and Response To Treatmentmentioning
confidence: 99%